Image segmentation of repetitive patterns / Kamelia Kamel - Kamel, Kamelia (2014)
Image segmentation is a challenging task in the area of image processing and has been researched for the last four decades. There are many research conducted on image segmentation, but a special attention needs to be focused on segmentation of images with repetitive patterns, as it involves grouping the repeated patterns in a meaningful structure. The objectives of this study is to propose a method to segment the repetitive patterns image and grouped the images based on its shape features. For this purpose, 7 Pua Kumbu images is selected. There are several steps involved throughout the proposed method.